ROLE OF THE TOURISM SECTOR IN ECONOMIC GROWTH AND JOB CREATION - Fachmi Tamzil (Jurnal Cinta Nusantara, 2023)
The tourism sector has long been recognized as one of the main pillars in driving a country's economic growth as well as creating significant employment opportunities. This study aims to analyze the role played by the tourism sector in supporting economic growth and job creation. Through a descriptive analysis approach, this study illustrates how the tourism sector can contribute to increasing Gross Domestic Product (GDP) through tourist consumption, investment in tourism infrastructure, and exports of tourism products. In addition to the economic impact, the tourism sector also has an important role in job creation. With the growth of this sector, various types of jobs are becoming available, ranging from accommodation, transportation, to other supporting service sectors. This increase in the number of jobs has directly contributed to reducing the unemployment rate and increasing people's welfare. However, challenges also arise along with the benefits generated by the tourism sector. In an effort to maintain sustainability, prudent management of environmental impacts, cultural protection, and the development of quality human resources in the tourism industry are needed. By understanding the role of the tourism sector in economic growth and job creation, governments and relevant stakeholders can design policies that support the development of this sector in a sustainable manner.